Rancang Bangun Prototype Sistem Kontrol Exhaust Fan Pada Smoking Room Menggunakan Metode Fuzzy Berbasis Arduino Uno - Teten Dian Hakim; Bayu Sudrajat (Teknik Elektro Universtias Krisnadwipayana, 2025)
There are still many people who do not use special rooms for smokers or smoking rooms because the air in the room is stuffy. This research aims to overcome this problem by designing a prototype exhaust fan control system in a smoking room using an arduino uno based fuzzy method. The fuzzy logic method is used to optimize exhaust fan speed settings based on the variables of smoke content, CO gas content and the number of people detected in the smoking room. This system uses several hardware devices such as the Arduino, sensor MQ-2, sensor MQ-7, and sensor proximity. Tests were carried out to verify system performance, including the output voltage of the MQ-2 and MQ-7 sensors regarding changes in smoke levels and CO gas levels, and the distance that can be detected by the proximity sensor, as well as the accuracy of the tool output by comparing the tool output results against MATLAB. The test results of the MQ-2 and MQ-7 sensors can obtain different output voltages at each PPM level. From testing the proximity sensor, the results showed that the proximity sensor can detect objects or the human body up to a distance of 30cm. From testing fuzzy logic with MATLAB, the results of comparing the tool's output value with the MATLAB output value were obtained with an accuracy of 99.673%, which can be concluded that the tool can work well.